KINERJA KELEMBAGAAN PEMASARAN KAKAO BIJI TINGKAT PETANI PERDESAAN SULAWESI TENGAH: KASUS DESA AMPIBABO KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Abubakar, Ihdiani; Yantu, Marwan; Asih, Dewi Nur (AGROTEKBIS, 2013)
The purpose of this study was to identify the characteristics of Cacao farmers in Ampibabo village e.g. the structure and cocoa market behavior at farm level and analyze the part of cocoa prices that received by farmers. Research areas defined as deliberate sampling, done by using simple random sampling with 30 farmers, 1 village trader, 2 district middlemen, 1 wholesaler and 1 cocoa exporter at Palu City as samples. Analysis tools used in this study were the marketing margins, Farmer´s Share analysis and description. Result showed that Cocoa marketing in Ampibabo village has an oligopsony labor market structure, and the marketing is an institutional market which controlled cacao farmers by setting up a contract agreement between farmers and traders, which contained several rules between these two parties and the contract, could be paid in several installments. There are two channels of marketing system was found in Ampibabo village, the first resulted to  90.24% of  cocoa bean price shared to farmer with  margin of  2, 000 IDR kg-1 while second system farmers received 87.80% of the price with margin of  2,500 IDR kg-1.